Relación de la estructura diamétrica y abundancia en bosque de colina baja, distrito de Balsapuerto, Loreto, Perú. 2023 - Ushiñahua Silvano, Jin Pool (2024)
The relationship between diameter structure and abundance was examined in the low hill forest of the district of Balsapuerto, Loreto, Peru. During the study, seven species belonging to four different botanical families were identified, comprising a total of seven genera. The tree density was 0,930 trees per hectare, of which 1141 were recorded. The species Iryanthera elliptica stood out with the highest number of trees (0,688 trees per hectare), followed by Cariniana multiflora with a density of 0,119 trees per hectare. A composite allometric model was used to fit the relationship between diameter structure and overall abundance (Y = 0,7865 * (0,9719^d)), as well as for the species Iryanthera elliptica (Y = 5,61796 * (0,93417^d)). The correlation between diameter structure and abundance was 0.749, indicating a negative relationship. This suggests that as diameter structure increases, tree abundance tends to decrease, and vice versa.